The Causative Factor of Men Low Interest in Becoming Contraception User - Rizka Mardiya and Ismarwati (International Journal of Advanced Science and Technology, 2020)
High level of fertility and low usage of modern contraception method among men still become a big problem until it is necessary to know what factors which cause men not using contraception. The method in arranging this scoping review used Arksey and O’Malley guidelien. The results obtained from 7 articles show that 71% use cross sectional method and there are 86% research from developing countries. The themes found in this review are educational factor, religion factor, information source factor, culture social factor, and age factor. There are many factors which cause low participation of men in using contraception.